math
posted by Liz [please... urgent!] .
given that c is the logarithm of x in base a, and d is the logarithm of x in base b, find the general statement that expresses the log of x ib base ab, in terms of c and d.
I couldn't include subscripts, but here are what the logs should look like: loga_x=c ; logb_x=d...logab_x = [in terms of c and d]
I have no clue where to start 8
Respond to this Question
Similar Questions

Review of Logs
I can't seem to get the answer to this; the answer key says log(base 8)6 Write as a single logarithm log(base 8)42log(base 8)3  log(base 8) 6 I'm hoping the key is wrong :) Thank you for your help! 
precalculus
given that c is the logarithm of x in base a, and d is the logarithm of x in base b, find the general statement that expresses the log of x in base ab, in terms of c and d. [*subscripts not included: a,b,ab] loga_x=c ; logb_x=d ...logab_x … 
math
if y is equal to the logarithm of x to the base 5, what is the logarithm of x to the base 25 in terms of y? 
Precalc
1. 1/3log base 8 of (x+1)=2log base 8 of 3(2/3)log base 8 of (x+1) 2. 2^x+8 times 2^=x all over 2 = 3 3. if log base a of 3= x and log base a of 2 = y, find each of thefollowing in terms of x and y log base a (18a^3) thanks!! 
math
Use the Laws of logarithms to rewrite the expression log(base 2)(11x(x9)) in a form with no logarithm of a product, quotient or power. After rewriting we will have: log(base 2)A+log(base 2)x+log(base 2)f(x) What is A and what is f(x)? 
Math
So I have a question regarding advanced functions, logarithm stuff. here is the question: Beginning with the function f(x) = log[base(a)]x ,state what transformations were used on this to obtain the functions given below: a) p(x) = … 
Algebra 2
Explain the difference between log base b (mn) and ( log base b of m)(log base b of n). Are they equivalent? 
Algebra 2
Express as a single logarithm. 1/2 log base b of (x2) log base b of y + (3 log base b of z) = log base 6 of (x2)^1/2 
Advanced Functions/ Precalculus Log
1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)xlog(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x1). … 
logarithm
If log base 2 of x and log base 2 of y are distinct positive integers and log base x of 2 plus log base y of 2 equal to 0.5. xy=?